PENGARUH BERMAIN GAME ONLINE MOBILE LEGENDS TERHADAP ETIKA BERKOMUNIKASI MAHASISWA MUSLIM - Mita Rosalina; Ilah Holilah; Tb Nurwahyu; Umdatul Hasanah; Nur Asia T (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2024)
This research is motivated by the popularity of online games that are currently very popular. One of them is the mobile legends game, which is very popular among students. Many students play this game besides being a hobby, it can also be a medium of entertainment that has an impact afterwards when playing. This study uses a quantitative approach method where the data presented is in the form of numbers. The research sample consisted of 95 respondents who were analyzed using the Slovin formula, data collection using the distribution of Likert scale model questionnaires, and analysis techniques using the help of SPSS software version 25. The results of this study indicate that there is an influence of playing mobile legends games on communication ethics among students of the faculty of da'wah UIN Sultan Maulana Hasanuddin Banten. This is shown by producing a hypothesis test with a calculated t value of 6.045 which exceeds the t table value of 1.661 and obtains a significant value of 0.000 where the significant value of 0.000 <0.05, so it can be concluded from these results that the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha). And the influence of playing online mobile legends games on communication ethics among students of the faculty of da'wah UIN Sultan Maulana Hasanuddin Banten.